Ergonomic risk management process for safety and health at work - Oleg Bazaluk; Vitaliy Tsopa; Serhii Cheberiachko; Oleg Deryugin; Dmytro Radchuk; Oleksandr Borovytskyi; Vasyl Lozynskyi; Vasyl Lozynskyi (Frontiers Media S.A., 2023)
PurposeThe paper aims to provide the main principles and practical aspects of the model, to present the process of identifying, determining the level, as well as assessing and managing occupational and ergonomic risks.MethodsTo conduct the research, as well as to identify the influence of various dangerous factors related to the working posture, pace, rhythm of work performance, equipment and individual characteristics of the employee's health condition, methods of complex analysis and synthesis, formal and dialectical logic are used to study the essence of the concept of occupational and ergonomic risks. Additionally, induction and deduction methods are used to examine the cause-and-effect relationships between dangers, dangerous factors, dangerous event, and the severity of consequences to determine the level of occupational and ergonomic risks based on the improved bow-tie model. The proposed approach effectiveness is tested based on the assessment of occupational and ergonomic risks of forest workers (loggers) with the participation of five experts to identify dangerous factors and develop precautionary measures.ResultsAn algorithm for managing occupational and ergonomic risks has been developed, consisting of eleven steps, which can be divided into three steps: preparatory, main and documented. It has been determined that occupational and ergonomic risk is the probability of a dangerous event occurring due to employee's physical overload and its impact on the severity of damage to the employee's physical health. The level of occupational and ergonomic risk management is determined taking into account the probability (frequency), intensity and duration of physical overload, as well as the employee's adaptation index to physical overload and his/her health index.ConclusionThe novelty is the substantiation of the principles of occupational and ergonomic risk management, which are based on the bow-tie model and predict the impact on the probability and severity of consequences of a dangerous event, taking into account dangerous factors. Forms for drawing up occupational and ergonomic risk maps have been developed, in which it is necessary to consider interaction of occupational hazards and occupational-ergonomic risk - physical overload.